Efficacy of Kumaun Himalayan Biota orientalis Endl. leaves extracts against pathogenic fungi - Joshi, Savita; Sati, S. C.; Kumar, Parikshit (International Journal of Pharmacology and Toxicology, 2016)
An increasing demand for natural plant products has shifted the attention from synthetic to natural antifungal agents. This study was   carried out to evaluate the antifungal activity of methanol, ethanol, chloroform, hexane and water extracts of Biota orientalis Endl. leaves, a Kumaun Himalayan gymnospermic plant. The antifungal potential of all extracts of B. orientalis were tested against seven different fungal strains (Alternaria alternata, Colletotrichum falcatum, Fusarium oxysporum, Pyricularia oryzae, Sclerotinia rolfsii, Sclerotinia sclerotiorum and Tilletia indica) using agar-well diffusion method. The ethanol extract was found most active against all the pathogens tested (Percent inhibition, 27-59%) followed by hexane extract (Percent inhibition, 31-58%) and methanol extract (27-57%) while     chloroform and aqueous extracts were found totally inactive against all the tested fungal strains, only chloroform extract showed       inhibitory activity against S. rolfsii (% inhibition, 58%). The inhibitory activity of these extracts was found very effective as compared to Clotrimazol, standard antifungal agent that was used as positive control against tested fungal strains.